The role of inspection of hydraulic structures in the assessment of their technical condition. Issue 1 (July 2020) - Kozlov, D; Yurchenko, A
Abstract: The development of the territory of Moscow has led to the need for a survey of water bodies and inventory of existing hydraulic structures, a thorough assessment of their technical condition, typifying the main types of structures, and determining their functional features. To solve these tasks, we used methods of field expedition survey, and analytical calculations of hydraulic structures, statistical methods of information processing, and analysis of available cartographic and technical documentation. A quantitative and qualitative analysis of the state of hydraulic structures located on the territory of New Moscow and their operating conditions was performed; the current level of their safety was assessed. It is proved that it is necessary to create a unified information database for all water bodies and hydraulic structures that have passed the survey, as well as to develop a simplified form of the act of pre-Declaration inspection of structures for which there is no functional and design information. It is shown that it is necessary to develop a plan of measures to ensure the safety of hydraulic structures without registered property rights.